Numerical Solution of the Gyroaverage Operator for the Finite Gyroradius Guiding-Center Model (Communications in Computational Physics, 2010)
In this work, we are concerned with numerical approximation of the gyroaverageoperators arising in plasma physics to take into account the effects of the finiteLarmor radius corrections. Several methods are proposed in the space configurationand compared to the reference spectral method. We then investigate the influence ofthe different approximations considering the coupling with some guiding-center modelsavailable in the literature.